Functional and structural characterization of Hyp730, a highly conserved and dormancy‐specific hypothetical membrane protein - Stewart Fannin; Jonathan Rangel; Abiodun P. Bodurin; Tannon Yu; Brandon Mistretta; Sujina Mali; Preethi Gunaratne; Steven J. Bark; Jerry O. Ebalunode; Arshad Khan; William R. Widger; Mehmet Sen (MicrobiologyOpen, 2021)
Abstract Membrane proteins represent major drug targets, and the ability to determine their functions, structures, and conformational changes will significantly advance mechanistic approaches to both biotechnology and bioremediation, as well as the fight against pathogenic bacteria. A pertinent example is Mycobacterium tuberculosis (H37Rv), which contains ~4000 protein‐coding genes, with almost a thousand having been categorized as ‘membrane protein’, and a few of which (~1%) have been functionally characterized and structurally modeled. However, the functions and structures of most membrane proteins that are sparsely, or only transiently, expressed, but essential in small phenotypic subpopulations or under stress conditions such as persistence or dormancy, remain unknown. Our deep quantitative proteomics profiles revealed that the hypothetical membrane protein 730 (Hyp730) WP_010079730 (protein ID Mlut_RS11895) from M. luteus is upregulated in dormancy despite a ~5‐fold reduction in overall protein diversity. Its H37Rv paralog, Rv1234, showed a similar proteomic signature, but the function of Hyp730‐like proteins has never been characterized. Here, we present an extensive proteomic and transcriptomic analysis of Hyp730 and have also characterized its in vitro recombinant expression, purification, refolding, and essentiality as well as its tertiary fold. Our biophysical studies, circular dichroism, and tryptophan fluorescence are in immediate agreement with in‐depth in silico 3D‐structure prediction, suggesting that Hyp730 is a double‐pass membrane‐spanning protein. Ablation of Hyp730‐expression did not alter M. luteus growth, indicating that Hyp730 is not essential. Structural homology comparisons showed that Hyp730 is highly conserved and non‐redundant in G+C rich Actinobacteria and might be involved, under stress conditions, in an energy‐saving role in respiration during dormancy.